Social Vulnerability and Ecological Fragility: Building Bridges between Social and Natural Sciences Using the Irish Potato Famine as a Case Study - Evan D. G. Fraser (Ecology and Society, 2003)
Between 1845 and 1850, a potato blight triggered a famine that killed or displaced 25% of the Irish population. Aside from its historical and cultural significance, the Irish Potato Famine illustrates how social and economic forces can create vulnerability to environmental disturbance. Therefore, studying the famine contributes to the on-going academic debate on theories to combine social and environmental data. This paper explores the conditions leading to the Irish famine using the "Entitlement" framework of Sen (1980) and the "Panarchy" model proposed by Gunderson and Holling (2002). Entitlement theory allows us to better understand how community food security may become vulnerable over time as different social and economic forces eliminate or restrict avenues to obtain food. In Ireland, a host of economic, demographic, and social pressures marked the decades leading to the famine and meant that the Irish peasantry had no food options when the potato crop failed. Panarchy provides a way of characterizing ecological systems that are vulnerable to disruptions. The agro-ecosystem that developed in Ireland prior to the famine had characteristics typical of vulnerable environments: fields were close together, biodiversity was low, and a large amount of biomass made this ecosystem attractive to opportunistic pests. Neither framework, however, provides an adequate way of examining the totality of human-environmental relations. By combining entitlements with panarchy, we can explore both the social and environmental characteristics of vulnerability. Entitlements and panarchy can be coupled by first assessing the extent to which communities depend on the natural environment for livelihoods, and the options available if the environment changes. Once a dependency on the environment has been ascertained, the characteristics of the specific ecosystems in question must then be assessed to determine their vulnerability to external shocks and disturbances. The panarchy framework makes this possible.